2001
DOI: 10.1038/88158
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors regulate the survival and fate of cells derived from human neurospheres

Abstract: Cells isolated from the embryonic, neonatal, and adult rodent central nervous system divide in response to epidermal growth factor (EGF) and fibroblast growth factor 2 (FGF-2), while retaining the ability to differentiate into neurons and glia. These cultures can be grown in aggregates termed neurospheres, which contain a heterogeneous mix of both multipotent stem cells and more restricted progenitor populations. Neurospheres can also be generated from the embryonic human brain and in some cases have been expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
198
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(219 citation statements)
references
References 33 publications
15
198
0
6
Order By: Relevance
“…Upon attachment, in the presence of serum, surface cells of neurosphere start to migrate away from the center then differentiate into neurons (β-tubulin III -red), astrocytes (GFAPgreen) and oligodendrocytes (data not shown). These results are consistent with the pattern of differentiation in neurospheres (Caldwell et al, 2001) or human embryonic stem cells (Benzing et al, 2006). Neural character of HUCB-NSC line was further evaluated by comparative analysis of the transcriptional profile (Affymetrix DNA microarray probes HG-U133, covering the expression of about 40.000 genes), between the free-floating, non-differentiated HUCB-NSC and its starting, nonselected cell populationmononuclear cell (MNC) fraction of human cord blood.…”
Section: Neurally-committed Cord-blood-derived Stem/progenitor Cells supporting
confidence: 62%
“…Upon attachment, in the presence of serum, surface cells of neurosphere start to migrate away from the center then differentiate into neurons (β-tubulin III -red), astrocytes (GFAPgreen) and oligodendrocytes (data not shown). These results are consistent with the pattern of differentiation in neurospheres (Caldwell et al, 2001) or human embryonic stem cells (Benzing et al, 2006). Neural character of HUCB-NSC line was further evaluated by comparative analysis of the transcriptional profile (Affymetrix DNA microarray probes HG-U133, covering the expression of about 40.000 genes), between the free-floating, non-differentiated HUCB-NSC and its starting, nonselected cell populationmononuclear cell (MNC) fraction of human cord blood.…”
Section: Neurally-committed Cord-blood-derived Stem/progenitor Cells supporting
confidence: 62%
“…20 It has been shown to bind neurotrophic factors, such as NGF and NT3, which are secreted by astrocytes. 21 We have previously shown that human NPC's express the trk C-receptor, 22 so binding of a-2 macroglobulin to NT3 secreted by astrocytes may be having a role in the neurite outgrowth seen with hippocampal and midbrain ACM. In addition, extracellular matrix glycoprotein, falls into the family of neurite promoting factors, so this too may be having a role in neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Spheroid culture methods of stem cells from different tissues have been successfully used for expansion of cardiac and neural stem cells. These spheres sensitize target stem cells to growth factors and provide sufficient cell-to-cell and cell-to-matrix contacts, mimicking the in vivo stem cell niche [3,4]. Here we asked whether spheroid culture of blood mononuclear cells (MNCs) would potentiate the expansion of circulating blood HSPC.…”
Section: Dear Editormentioning
confidence: 99%